Surgical management of hemothorax due to blunt chest trauma - S. A. Plaksin; D. N. Ponomarev; A. J. Sozkov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to analyze the results of treatment and improvement of surgical management of hemothorax following blunt chest injury.METHODS AND MATERIALS. Of 398 patients with blunt chest trauma, 84 (21.1 %) had hemothorax. Patients were divided into 4 groups: small hemothorax (<300 ml) – 43 people (51.1 %); medium (300 to 1000 ml) – 27 (32.1 %), large (1000 to 1500 ml) – 10 (11.9 %); and total (>1500 ml) – 4 (4.8 %).The causes were household injuries – in 50 cases (59.5 %) and transport injuries – in 20 cases (23.8 %).RESULTS. Medium, large and total hemothorax was diagnosed by chest X-rays. Computed tomography was performed in case of severe concomitant injuries, clotted hemothorax and unclear diagnosis. In the Group 1, hemothorax was diagnosed by computed tomography scans only in 12 cases (27.9 %), by ultrasound examination – in 4 cases (9.3 %). Medium and large hemothorax at late admission was removed by pleural puncture in 5 cases. Pleural drainage was performed in 24 patients. Thoracoscopy was performed in 53 patients. In 32 patients (60%) of Groups 1 and 2, thoracoscopy ended only with a revision of the pleural cavity and blood removal. The clotted hemothorax was removed during thoracoscopy in 15 patients of Groups 2, 3 and 4. With total hemothorax, 2 patients underwent thoracotomy for ongoing bleeding. Thoracotomy was performed in 3 patients of Groups 1 and 2 for ruptures of the lung and diaphragm. The cause of hemothorax could be rib fractures in 75 patients (90.4 %), lung rupture in 49 patients (59 %) with hemopneumothorax, damage to the diaphragm in 3 (3.6 %) cases. Surgical hemostasis for ongoing bleeding was required in 7 (8.4%) cases. Thoracoscopy for residual hemothorax after drainage of the pleural cavity was performed in four (4.8%) patients.CONCLUSION. Surgical management for traumatic hemothorax should be differentiated depending on its volume, the associated injuries, the time from injury to the start of treatment, and the developed complications.